Efficacy of virginiamycin as a prophylactic drug to prevent swine dysentery - D A Schoneweis; G A Kennedy (Kansas Agricultural Experiment Station Research Reports, 1973)
Forty-eight feeder pigs were used in an experiment to determine Virginiamycin's effectiveness in preventing swine dysentery. Thirteen of 24 controls and one of 24 that received the antibiotic at either 25 or 50 grams per ton of feed died of swine dysentery or complications. Feed conversion ratio was markedly improved by the antibiotic. Virginiamycin was judged effective in preventing clinical cases of swine dysentery, but it has not been cleared for use in swine. Swine dysentery, also known as bloody dysentery, vibrionic dysentery, bloody scours, or black scours, is a infectious, enteric disease of swine. It is serious in many areas of the Midwest and is assumed to be present wherever swine are raised in the United States. For years the etiology of the condition was thought to be Vibrio coli; however, recent work has indicated Treponema hyodysenterrae-instead.; Swine Day, Manhattan, KS, November, 1973
Keywords: Swine day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 203; Swine; Virginiamycin; Prophilactic drug; Swine dysentery